Target engagement and cellular fate of otelixizumab: a repeat dose escalation study of an anti‐CD3ε mAb in new‐onset type 1 diabetes mellitus patients. Issue 4 (5th February 2019) - Vlasakakis, Georgios; Napolitano, Antonella; Barnard, Ruth; Brown, Kim; Bullman, Jonathan; Inman, David; Keymeulen, Bart; Lanham, David; Leirens, Quentin; MacDonald, Alexander; Mezzalana, Enrica; Page, Kevin; et al.
Abstract : Aims: This paper describes the pharmacological findings from a study where otelixizumab, an anti‐CD3ɛ mAb, was dosed in new onset Type 1 diabetes mellitus (NOT1DM) patients. This is the first time that the full dose–response of an anti‐CD3ɛ mAb has been investigated in the clinic. The data have been validated using a previously developed pharmacokinetic/pharmacodynamic (PK/PD) model of otelixizumab to simulate the interplay between drug administration, CD3ɛ target engagement and downmodulation. Methods: Patients were randomized to control or active treatment with otelixizumab (1:4), administered via infusion over 6 days, in a dose‐ascending study consisted of three cohorts ( n = 10 per cohort) at doses of 9, 18 or 27 mg respectively. The study allowed quantification of otelixizumab PK, CD3ɛ target engagement and its pharmacodynamic effect (CD3ε/TCR modulation on circulating T lymphocytes). Results: Otelixizumab concentrations increased and averaged to 364.09 (54.3), 1625.55 (72.5) and 2781.35 (28.0) ng ml −1 (Geom.mean, %CV) at the 9, 18 and 27 mg dose respectively. CD3ɛ target engagement was found to be rapid (within the first 30 min), leading to a receptor occupancy of 60% within 6 h of dosing in all three doses. A dose–response relationship was observed with the two highest doses achieving a 90% target engagement and consequential CD3ɛ/TCR downmodulation by Day 6. Conclusions: Data from this study revealed maximum target engagement and CD3ɛ/TCR modulation is achieved at doses of 18, 27 mg of otelixizumab. These findings can be useful in guiding dose selection in clinical trials with anti‐CD3ɛ mAbs.